KEWENANGAN DEWAN PENGAWAS KPK DALAM MEMBERI IZIN PENYADAPAN - M Ali Imron, (2021)
Based on the 1945 Constitution Article 1 paragraph (3) which reads: Indonesia is a constitutional state. This has a consequence that every implementation of state administration in Indonesia must be based on applicable legal regulations or what is commonly referred to as legal supremacy. The Corruption Eradication Commission, also known as the KPK, is a state institution that in carrying out its duties and authorities is independent and free from the influence of any power. The KPK was established and worked based on Law Number 30 of 2002 concerning the Corruption Eradication Commission, which was later amended by Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission (hereinafter referred to as UU KPK). The revision of the Corruption Eradication Commission Law has attracted enough public attention because of the new provisions, namely the existence of a KPK supervisory board. The public's attention was caught because many thought that the KPK supervisory board instead of supervising the KPK's performance was considered to be able to weaken the KPK. The main problem with the revision of the KPK Law is then used as the basis for the formulation of problems in this paper relating to the position of the Supervisory Board. Based on the results of the research that has been done, it turns out that the position of the Supervisory Board which is considered to weaken the KPK institution is not true. The KPK is still able to maintain its existence, even though the KPK's wiretapping authority in carrying out its function of investigating corruption cases must first obtain permission from the Supervisory Board. This can be proven by the arrest of several suspects in corruption cases recently who have been arrested under Hand Catch Operation (OTT), such as the alleged bribery case for the lobster seed export license that ensnared the former Minister of Maritime Affairs and Fisheries Edhy Prabowo and the Cimahi Mayor case. In fact, the KPK Supervisory Board's authority in granting permits and supervising the investigation and investigation processes, especially those related to the Hand Arrested Operation (OTT) carried out by the KPK, has become more prundent and accountable.